Estonia as an engine of integration: The Estonian parliament sets a clear course in the constitutional debate - Daniela Kietz; Andreas Maurer (Stiftung Wissenschaft und Politik (SWP), 2006)
On 8 February 2006 the Estonian parliament endorsed at first reading a law to ratify the Constitutional Treaty of the European Union (EU) against the background of intensifying debate on the future of the Treaty. Final Estonian ratification is due to take place before the end of Austria's EU Presidency in June 2006. There is good reason for taking the decision at precisely that point in time. Almost all heads of state and government have now presented their divergent starting points for the debate of the coming months - from Angela Merkel's proposal of a supplementary protocol on the social dimension of the EU to Jacques Chirac's plea for implementation of only a few parts of the Treaty. But it is still far from clear what the procedure should be with the Treaty, what chances of success the different conceivable options have, and along which lines a compromise is likely to emerge. (SWP-Comments / SWP)
Keywords: 320